Ubiquitin-Proteasome System–Regulated Protein Degradation in Spermatogenesis - Yi Xiong; Chao Yu; Qianting Zhang (Cells, 2022)
Spermatogenesis is a prolonged and highly ordered physiological process that produces haploid male germ cells through more than 40 steps and experiences dramatic morphological and cellular transformations. The ubiquitin proteasome system (UPS) plays central roles in the precise control of protein homeostasis to ensure the effectiveness of certain protein groups at a given stage and the inactivation of them after this stage. Many UPS components have been demonstrated to regulate the progression of spermatogenesis at different levels. Especially in recent years, novel testis-specific proteasome isoforms have been identified to be essential and unique for spermatogenesis. In this review, we set out to discuss our current knowledge in functions of diverse USP components in mammalian spermatogenesis through: (1) the composition of proteasome isoforms at each stage of spermatogenesis; (2) the specificity of each proteasome isoform and the associated degradation events; (3) the E3 ubiquitin ligases mediating protein ubiquitination in male germ cells; and (4) the deubiquitinases involved in spermatogenesis and male fertility. Exploring the functions of UPS machineries in spermatogenesis provides a global picture of the proteome dynamics during male germ cell production and shed light on the etiology and pathogenesis of human male infertility.